Desenvolvimento de módulo de detecção de miRNA para dispositivo biomédico de triagem de câncer - Carvalho, Dionísio Dias Aires de (2021)
Cancer is a set of diseases, malignant or benign neoplasms, associated with the disordered growth of cells, which can be aggressive and cause death. There are different types of cancer due to the variety of cells in the human body and their ways of reproducing and multiplying, thus affecting the severity and form of weakening tissues and organs. Diagnosis is performed with high-cost equipment and the need for specialized professionals to operate them, which leads to scarcity that delays the discovery of the disease and reduces the chances of survival for patients. However, in constant evolution, science has discovered new forms of detection, such as one of the most recent, micro RNAs (miRNAs), which are key regulators of gene expression, which act in blocking and regulating the action of messenger RNA, being potential biomarkers for the disease. The methodology uses a study on cancer and miRNAs as possible Biomarkers and a study on some types of biosensors in use today with the objective of finding a way that suits portability and low-cost parameters. The development of the project took place through simulation of the circuit in a computational system and its subsequent real construction. In all these steps, the need for integration with the information management system and task organizer was considered. This study provided subsidies for the development of a device with an embedded system that performs the reading and quantification of miRNA residues in order to ensure high specificity, being controllable by an external system through serial communication, which performs the test quickly and low cost, providing greater savings to SUS. It is concluded that the miRNA-Box, a device with an embedded system for biomedical use, developed by the Advanced Technological Innovation Nucleus (NAVI) in partnership with the Laboratory for Technological Innovation in Health (LAIS) and the Ministry of Health (MS), proposes the applicability in Primary Health Care (PHC) in order to perform the analysis and early diagnosis of breast, prostate and cervical cancer, in order to improve the patient screening process and provide cost reduction in the area of health with complex diseases.